Analisis Kebijakan Otonomi Pendidikan di Indonesia: Analysis of Education Autonomy Policy in Indonesia - Muslim Afandi; Rizki Erdayani; Syed Agung Afandi; M Rafi (Program Studi Ilmu Pemerintahan Fisip Universitas Mulawarman, 2022)
This study aims to analyze the autonomy policy of education in Indonesia. This study uses a qualitative approach with library research techniques. The results of this study indicate that the increase in the education budget allocation has not been able to increase the competitiveness of national education in the global arena. The implementation of educational autonomy through the establishment of various policies, including school-based management and the independent campus policy aims to give authority to educational institutions to provide flexibility in the management of education. Although the education autonomy policy has been able to increase the national education participation rate, this policy also raises new problems such as policy conflicts between the central government, regional governments, and educational institutions, inefficiency in education management, the occurrence of new corrupt practices, and education policies that tend to be top-down. The conclusion is that although it is in line with the demands of reform, education autonomy in Indonesia does not necessarily improve the quality of national education.